Emancipatory Aspects of Working Time Regulation - Risak, Martin (Momentum Quarterly, 2016)
The arguments for regulating working time are manifold: health and safety, fighting unemployment, the fair distribution of efficiency gains and self-determination of the worker. The article first develops the argument why limiting the freedom to work endlessly can be seen as emancipatory and then shows how emancipatory arguments played a role in justifying working time legislation since the late 19th century by using the explanatory notes to draft legislation as well as transcripts of parliamentary debates.